2009
DOI: 10.1177/0146167209346303
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Feel Worse to Look Their Best? Testing the Relationship Between Self-Esteem and Fertility Status Across the Menstrual Cycle

Abstract: Two studies measured self-esteem across the menstrual cycle to test the prediction that self-esteem will vary interindividually as a positive function of mate value and intraindividually as a negative function of fertility status. Study 1 (n = 52) found that self-esteem was positively related to mate value between women but that women experienced a self-esteem decrease nearest to ovulation, when women tend to be more attractive to men. Study 2 (n = 59) replicated these results and demonstrated that the self-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 60 publications
(84 reference statements)
0
34
1
Order By: Relevance
“…There are multiple possibilities that would be highly consistent with our theoretical perspective. For example, ovulating women might feel more comfortable with their bodies or another possibility is that ovulating women might feel more competitive and desire to seek status (Hill and Durante 2009). These and other possibilities 30 represent possible proximate-level mechanisms for how ovulation might influence behavior, whereby each proximate-level mechanism is consistent with our ultimate-level explanation for the existence of ovulatory shift effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…There are multiple possibilities that would be highly consistent with our theoretical perspective. For example, ovulating women might feel more comfortable with their bodies or another possibility is that ovulating women might feel more competitive and desire to seek status (Hill and Durante 2009). These and other possibilities 30 represent possible proximate-level mechanisms for how ovulation might influence behavior, whereby each proximate-level mechanism is consistent with our ultimate-level explanation for the existence of ovulatory shift effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, some research suggests that women with PMS have generally lower self-esteem scores than non-clinical controls (Morse et al1988) and therefore may have less stable self-esteem generally (Thewissen et al 2008). Hill and Durante (2009) investigated a non-clinical population of 52 undergraduate students, finding that self-esteem was higher at the least fertile phase of the cycle (late luteal phase), and low around the five days before and two days after ovulation (the most fertile point of the cycle). However, Edmonds et al (1995) found that self-esteem was not related to the menstrual cycle in their sample of 68 college students There is a considerable body of literature indicating that both anxiety and depression are exacerbated in the few days before and during menstruation (Clayton 2008).…”
Section: Self-esteem and The Menstrual Cyclementioning
confidence: 99%
“…An important aspect of self-esteem is individuals' mate value, both self-perceived and as perceived by others (Hill & Durante, 2013). Mate value indicates how attractive someone is as a potential mate (Brase & Guy, 2004).…”
Section: Self-esteemmentioning
confidence: 99%
“…Mate value indicates how attractive someone is as a potential mate (Brase & Guy, 2004). In order to increase mate value, self-enhancements such as working out and acquiring new clothes can be used (Brase & Guy, 2004;Hill & Durante, 2013;Park & Manner, 2009). Individuals in romantic relationships are less likely to use self-enhancements, and they tend to have higher self-esteem than those without significant others (Brase & Guy, 2004;Hill & Durante, 2013).…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation